Fundamental Rights of Corporations as International Human Rights: The Perspective of Regional Economic Courts - Wiater-Hellgardt, Patricia (Human Rights Law Review, 2023)
The article deals with the question of whether and why international human rights law should protect corporations at the example of regional economic integration systems such as the European Union. For the European Court of Justice, granting human rights to corporations is the natural response to the key role that private companies play in the integration program. Regional human rights courts, in contrast, partly struggle to recognise corporations as human rights holders. The article critically examines the theoretical raison d’être of fundamental rights of corporations, granted in the framework of international human rights, and reflects on them on the basis of a Rule of Law-postulate.
CRIS-Team Scopus Importer:2023-11-24
Keywords: European Union; fundamental rights; K E Y W O R D S: corporations; regional economic integration; regional human rights protection; Rule of Law